SCIENTIFIC REASONING ABILITY OF HIGH SCHOOL STUDENTS IN PALANGKA RAYA IN PHYSICS LEARNING - Dinata, Pri Ariadi Cahya; Lukas, Rensi; Hartanto, Theo Jhoni; Sari, Desy Kumala (Universitas Labuhanbatu, 2025)
Purpose-Scientific reasoning is an essential ability in learning science, including physics. This study aims to assess the scientific reasoning abilities of high school students in Palangka Raya City, focusing on six indicators: conservation reasoning, proportional reasoning, variable control, probabilistic reasoning, correlation reasoning, and hypothetical-deductive reasoning.Methodology-To achieve the goals, descriptive research consisted of 187 samples from six schools in two districts using the multistage stratified random sampling method. The instrument used in this study is Lawson's Classroom Test of Scientific Reasoning (LCTSR), containing twelve multiple-choice items. The data were analyzed using the Kruskal-Wallis test to determine the differences in average scores between schools, and descriptive statistics were used to describe students' general scientific reasoning skills. The analysis results show a p-value of 0.001, indicating that the test detected a statistically significant difference in the average score of scientific reasoning ability among high school students in the sample schools in Palangka Raya City.Findings-The descriptive analysis results showed that the conservation reasoning indicator had the highest percentage of correctness, while hypothetical-deductive reasoning was the least mastered by students. Additionally, most students are in the concrete operational thinking phase, despite having theoretically reached the formal operational phase in terms of cognitive development.Contribution-This finding has implications for educators in designing physics learning strategies that encourage the development of students' scientific reasoning as they progress toward the formal operational phase.